PEMBERIAN IZIN PEMBANGUNAN MINI MARKET PADA PT. INDOMARCO PRISTAMA TANPA PENINJAUAN LAPANGAN OLEH BADAN PELAYANAN PERIZINAN TERPADU SATU PINTU DI KOTA SAMARINDA - Arini Melindha Wijaya (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT This study entitled " Pemberian Izin Pembangunan Mini Market Pada PT. Indomarco Prismatama Tanpa Peninjauan Lapangan Oleh Badan Pelayanan Perizinan Terpadu Di Kota Samarinda ". The main issues examined in this study are: first, What is the requirements which is required by the government of Samarinda to control the establishment of minimarket in its territory? second, what is the Legal Action taken by the Government of Samarinda about the violation of letter of business market permission, if the permit were granted without any review by the authority? This study is included normative juridical research, by reviewing the related licensing, regulations applicable law, including the norms and principles contained there in. Based on the analysis the researchers did in order to address issues raised in this study, it can be concluded as follows: first, implement the concept through policies that stipulated in Peraturan Presiden RI No. 112 Tahun 2007 tentang Penataan dan Pembinaan Pasar Tradisional, Pusat Perbelanjaan, Toko Modern and Rancangan Perda Kota Samarinda (later become local regulations) on 2015 About Penataan dan Pembinaan Pasar Tradisional, Pusat Perbelanjaan, dan Toko Modern. . Legal action taken by the Government of Samarinda  about the violation of letter of business market permission, if the permit were granted without any review by related agencies are administrative actions and criminal actions.Keywords : Licensing, Market Competition, Retail Companies